2016
DOI: 10.1021/acs.est.5b04282
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Promotes Chloropicrin Formation by Oxidizing Amines to Nitro Compounds

Abstract: Chloropicrin formation has been associated with ozonation followed by chlorination, but the reaction pathway and precursors have been poorly characterized. Experiments with methylamine demonstrated that ozonation converts methylamine to nitromethane at ∼100% yield. Subsequent chlorination converts nitromethane to chloropicrin at ∼50% yield under the conditions evaluated. Similarly high yields from other primary amines were limited to those with functional groups on the β-carbon (e.g., the carboxylic acid in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…For precursors containing an amine-group, the combined ultraviolet (UV)/chlorine treatment could oxidize the amine-group to a nitrogroup, which is always a rate-limiting step for the formation of HNMs (Deng et al, 2014). Ozonation also led to a promoted TCNM formation and primary and secondary alkyl amines are the predominant precursors (McCurry et al, 2016). UV irradiation has been recognized as a promising disinfection means because it neither requires additional chemical(s) nor impairs the aesthetic quality (e.g., taste and odor) of treated water and wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…For precursors containing an amine-group, the combined ultraviolet (UV)/chlorine treatment could oxidize the amine-group to a nitrogroup, which is always a rate-limiting step for the formation of HNMs (Deng et al, 2014). Ozonation also led to a promoted TCNM formation and primary and secondary alkyl amines are the predominant precursors (McCurry et al, 2016). UV irradiation has been recognized as a promising disinfection means because it neither requires additional chemical(s) nor impairs the aesthetic quality (e.g., taste and odor) of treated water and wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…HANs, including dichloroacetonitrile (DCAN), trichloroacetonitrile (TCAN), bromochloroacetonitrile (BCAN), and dibromoacetonitrile (DBAN) are often detected in chlorinated water [12]. Trichloronitromethane (TCNM) is the most important HNM that is often identified in chlorinated water [13,14].Nitrogenous organic compounds (NOC) play an important role in providing precursors to generate N-DBPs, such as HANs and HNMs, during chlorination [15,16]. Amino acids (AAs) are the most studied subclass of NOC; they are found widely in fresh waters and are difficult to remove using traditional drinking water treatment processes [17].…”
mentioning
confidence: 99%
“…For amines ( Figure 6.6c), an ozone adduct on the nitrogen atom leads to formation of N-oxide for tertiary amines and hydroxylamine for primary and secondary amines (von Gunten 2003a) (see also Chapter 4). A recent study also reported formation of nitromethane from ozonation of methylamine (McCurry et al 2016).…”
Section: Results Andmentioning
confidence: 86%
“…The formation potentials of HAN4 and THAMs decreased 30 to 41% and 20 to 32%, respectively, when the specific ozone dose increased from 0.4 to 1 mg O 3 /mg DOC. Although the differences in concentrations after ozonation did not reach statistical significance (p>0.05), the decreasing trend in formation potentials at higher ozone dose suggests favorable oxidation of HAN4 and THAM precursors to nitroalkane groups which in turn promotes THNM formation (Huang et al 2012, McCurry et al 2016, Yang et al 2012b). These reactions may explain the significant increase in THNM formation potentials from 0.005 to 0.060 µmol/mmol C when ozone dose was increased.…”
Section: Ozonation Phmentioning
confidence: 90%
See 1 more Smart Citation